2022
DOI: 10.2174/18744346-v16-2112230
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Urogenital Infection Educational Program on Women Knowledge and Practices

Abstract: Background: Urogenital infection is generally regarded as a silent epidemic. It is one of the major public health problems among women that causes a considerable proportion of gynecological morbidity and maternal mortality in developing countries. Aim: The aim of this study is to evaluate the effect of an educational program on women’s knowledge and practices about urogenital infection. Methods: A quasi-experimental research design wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…According to another study done by Sayed et al, only a 50% positive response rate was observed in the cleaning of perineum from front to back and 28% rate for wearing cotton underwear. 26 Although 98.7% of teachers in the present investigation believed that the cleanliness of underwear is an important fact to care about, a considerable number of them tended to dry their underwear under shade or a fan, given the need of an educational program regarding such poor practices. This practice has to be discouraged since it is recommended to use direct sunlight for drying underwear whenever possible.…”
Section: Discussionmentioning
confidence: 57%
“…According to another study done by Sayed et al, only a 50% positive response rate was observed in the cleaning of perineum from front to back and 28% rate for wearing cotton underwear. 26 Although 98.7% of teachers in the present investigation believed that the cleanliness of underwear is an important fact to care about, a considerable number of them tended to dry their underwear under shade or a fan, given the need of an educational program regarding such poor practices. This practice has to be discouraged since it is recommended to use direct sunlight for drying underwear whenever possible.…”
Section: Discussionmentioning
confidence: 57%
“…However, the present study contradicts the findings of Sayed et al . [ 27 ], who reported a high positive correlation between the total level of self-care practices during the pretest, highlighting the need for more research to better understand the factors affecting self-care practices.…”
Section: Discussionmentioning
confidence: 99%